Identification of drug(s) selectively targeting colorectal cancer stem-like cells for differentiation (differentiation therapy) - Ahmed, Mehreen (2020)
Increasing evidence suggests that cancer cell populations contain a small proportion of cells that have the unique self-renewal, tumour-initiating and limited differentiation ability that allow them to resist the therapies and promote cancer recurrence. Therefore, undifferentiated cancer stem-like cells are of major therapeutic interest specially to devise novel diagnostic and therapeutic agents. Herein, the aim of this study is to identify compound(s) that are able to target colorectal cancer stem-like cells by inducing differentiation.